Modeling and Simulation of Internal Faults in Salient-pole Synchronous Generators with Wave Windings - Sinha A.; Vishwakarma D.N.; Srivastava R.K. (My University, 2025)
When an internal fault occurs in the wave-connected windings of salient-pole synchronous generators, the symmetry between the parallel windings is broken, and different currents flow in them since unsymmetrical magnetic linkage exists between the stator windings. The aim of this article is to present a model to investigate the internal fault currents in large hydrogenerators with wave windings. This model is based on a modified winding function approach, where the machine inductances are calculated directly from the machine winding distribution, and the space harmonics produced by them are also taken into account. The calculation of the machine inductances are made easier by the use of machine electrical parameters instead of geometrical parameters. The fast Fourier transform analysis of the simulated results has been tabulated for different cases of internal faults. By using the simulated internal fault data, suitable numerical protection schemes for hydrogenerators can be developed.